Spreading Husband-Wife Disgrace on Social Media: A Quranic Perspective - Falah, Mohammad Bachrul; Ramadan, Taufan Fuad (Abdurrauf Journal of Islamic Studies, 2025)
The prevalent phenomenon of spreading spousal disgrace on social media raises significant concerns regarding communication ethics and poses a threat to marital harmony, while also disregarding Islamic values of privacy. This study aims to analyze the phenomenon of spreading spousal disgrace on social media from a Quranic perspective. Q.S. An-Nur: 19 is used as an analysis of the problem. Some books of tafsir as primary data serve to strengthen the argument. Secondary data were obtained from several books of tafsir and related scientific literature. The results of the study show that spreading a spouse's disgrace is inconsistent with the principles of Q.S. An-Nur (24): 19. The Qur'an offers two solutions, namely preventive and practical solutions. This paper shows that the Quran and its interpretation can be used to answer various problems related to digital transformation. Through this study, the Qur'an is expected to be a reference in solving contemporary issues. [Maraknya fenomena pengumbaran aib pasangan di media sosial menimbulkan problem etika komunikasi dan ancaman terhadap keharmonisan rumah tangga, sekaligus mengabaikan nilai-nilai privasi dalam Islam. Penelitian ini bertujuan untuk menganalisis fenomena pengumbaran aib pasangan di media sosial perspektif Al-Qur’an. Penelitian kepustakaan digunakan untuk memetakan dan menganalisis penelitian ini. Q.S. An-Nur (24): 19 digunakan sebagai analisis masalah. Beberapa kitab tafsir sebagai data primer berfungsi untuk memperkuat argumen. Data sekunder diperoleh dari beberapa kitab tafsir dan literatur ilmiah terkait. Hasil penelitian menunjukkan bahwa menyebarkan aib pasangan tidak sesuai dengan prinsip-prinsip dalam Q.S. An-Nur: 19. Al-Qur'an menawarkan dua solusi, yaitu solusi preventif dan solusi praktis. Tulisan ini menunjukkan bahwa Al-Qur'an dan tafsirnya dapat digunakan untuk menjawab berbagai persoalan terkait transformasi digital. Melalui kajian ini, Al-Qur'an diharapkan dapat menjadi rujukan dalam menyelesaikan masalah-masalah kontemporer.]